Prevalensi Strain Avian Pathogenic Escherichia coli (APEC) Penyebab Kolibasilosis pada Burung Puyuh - Wahyu Prihtiyantoro; Khusnan Khusnan; Mitra Slipranata; Imron Rosyidi (Jurnal Sain Veteriner, 2019)
Avian Pathogenic Escherichia coli (APEC) is a pathogen that causes colibacillosis in poultry, including salpingitis, omphalitis, cellulitis, swollen head syndrome, coligranuloma yolk sac inflammation, and air sacs inflammation. APEC is a zoonotic strain which spread through raw meat and processed meat products of animals and birds. In this research, the isolation and identification of Escherichia coli were done by using selective media MacConkey, Kligger Iron Agar, and Gram staining. Polymerase chain reaction (PCR) was used to analyse genetopically to detect 16SrRNA genes, vt1 genes, and vt2 genes. Thirty one (55,36%) isolates of 56 specimens collected from quail were detected as Escherichia coli. The detection of APEC strains towards 31 Escherichia coli isolates were done by using polymerase chain reaction (PCR) with vt1 and vt2 specific primer. The results showed that 32,26% (10/31) was APEC strains and 67.74% was non-APEC strains. From 10 isolates, 90% had vt1 gene and 10% had vt2 gene. Escherichia coli isolates were found in eyes (32,26%), infraorbital sinus fluid (32,26%), nasal fluid (16,20%), also in lungs, air sacs, ascites, and heart for 3,2% each. The isolates could not be found in the specimens from the skull. As a zoonotic agent, the isolates have an impact on human health.